Type 1 diabetes-related distress: Current implications in care - Rodríguez-Muñoz, Alba; Picón-César, María José; Tinahones-Madueño, Francisco José; Martínez-Montoro, José Ignacio (Elsevier, 2024)
Type 1 diabetes (T1D) is a complex chronic disease associated with major health and economic consequences, also involving important issues in the psychosocial sphere. In this regard, T1D-related distress, defined as the emotional burden of living with T1D, has emerged as a specific entity related to the disease. Diabetes distress (DD) is an overlooked but prevalent condition in people living with T1D, and has significant implications in both glycemic control and mental health in this population. Although overlapping symptoms may be found between DD and mental health disorders, specific approaches should be performed for the diagnosis of this problem. In recent years, different DD-targeted interventions have been postulated, including behavioral and psychosocial strategies. Moreover, new technologies in this field may be helpful to address DD in people living with T1D. In this article, we summarize the current knowledge on T1D-related distress, and we also discuss the current approaches and future perspectives in its management.
Keywords: Diabetes; Asistencia sanitaria; Salud mental; Type 1 diabetes; Diabetes distress; Clinical care; Mental health; Diabetes technology